Age-related differences in how negative emotions influence arithmetic performance. Issue 7 (3rd October 2021) - Lallement, Camille; Lemaire, Patrick
ABSTRACT: In this study, we investigated the role of negative emotions on arithmetic and whether this role changes with aging during adulthood. Young and older adults were asked to verify one-digit addition problems (Experiment 1) and to estimate the results of two-digit multiplication problems (Experiment 2). In both experiments, easier and harder problems were displayed superimposed on emotionally neutral (e.g. mushrooms) or emotionally negative (e.g. a corpse) pictures. In both simple and complex arithmetic, young and older adults obtained poorer arithmetic performance under negative emotion conditions, especially while solving harder problems. Most interesting, deleterious effects of negative emotions on arithmetic performance were larger in young than in older adults. These findings have important implications for further our understanding of the role of negative emotions in the domain of arithmetic and age-related differences in this role.